Analisis Pertumbuhan Mendekati Kapasitas Terhadap Status Gizi Anak dengan Model Logistik - Aprilia, Rima; Siregar, Aulia Rahman; Fernanda, Fariz Hakim; Suhendra, Irfan; Siregar, Nurmala Sari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The prevalence of malnutrition in children under five in Indonesia shows an estimate of future nutritional status based on current and past trends. A logistical population model is used in this study, which assumes that at some point in time, the population will reach equilibrium. The purpose of this study is to analyze the nutritional status of children under five aged 0-23 months in 2027 (t=9) using a logistics model. The data used came from the Central Statistics Agency (BPS) between 2016 and 2018, and is predicted for the period 2019 to 2027, assuming that the capacity limit (k) is 10,611.02. This study shows that type I and II logistics models can be used accurately to understand near-capacity growth related to children's nutritional status. The analysis shows that by 2027, it is estimated that there will be 359.35 children under five who will achieve optimal nutritional status.